Analysis of Capital Structure and Debt Ratio to Company Financial Performance - Ramadanti, Indah; Kurniawan, Rudy; Muhsin, Muhsin (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Sources of funding that can be used by companies include equity and debt. Companies that have high leverage in their capital structure may be more vulnerable to financial problems if interest rates rise or if company revenues decline. The purpose of this study is to analyze the effect of capital structure and debt ratio on financial performance in food and beverage companies listed on the IDX in 2019-2023. The method used in this study is a quantitative method. The analysis technique is multiple linear regression with the help of SPSS version 29. Sampling in this study used purposive sampling of 26 companies in the 2019-2023 period and produced 130 observation data. The results of this study are that Debt toEquity Ratio (DER) partially has a positive and significant effect on financial performance (ROA), Long Term to Debt Equity Ratio (LTDER) partially has a positive and significant effect on financial performance (ROA), and Debt to Assets Ratio (DAR) partially has a negative and insignificant effect on financial performance (ROA).